Enhancing Embankment Stability Assessment in Mining Operations through Fiber Optic Instrumentations: A DMAIC Approach - Leonardo, Samuel; Okdinawati, Liane (Indonesian Journal of Multidisciplinary Science, 2023)
This paper proposes a comprehensive solution to enhance embankment stability assessment in mining company's tailings management operations through the implementation of Fiber Optic instrumentations. The current monitoring solutions lack real-time capabilities, hindering timely assessment and mitigation of embankment stability issues. Fiber Optic cables provide sensing capabilities to detect vibrations and measure temperature variations, enabling early detection of structural issues within embankments. Real-time monitoring allows continuous assessment and immediate identification of potential risks. Implementing fiber optic cable instrumentations enhances embankment stability assessment, ensuring safety and minimizing failures. Data-driven decision-making is empowered through accurate and real-time data, enabling efficient resource allocation. The implementation follows a DMAIC (Define, Measure, Analyze, Improve, Control) approach, ensuring a comprehensive analysis and step-by-step plan. In conclusion, fiber optic cable instrumentations offer valuable enhancement to embankment stability assessment in mining's tailings management operations. Real-time monitoring, accuracy, and precision contribute to proactive measures and improved decision-making. Implementing this solution strengthens embankment stability practices, safeguards surrounding areas, and maintains regulatory compliance, fostering resilience and sustainability in mining operations.